Vitimização policial : estudo sociológico das violências sofridas por integrantes da Polícia Militar do Estado de Mato Grosso durante o período de folga - Cabelho, Victor Hugo (2024)
This research analyzes the police victimization in the Military Police of Mato Grosso (PMMT) occurred during the vacation period and its consequences at the institutional (macro) and individual level of the military police officer (micro). The research problem is: the institutional level of Mato Grosso Military Police (macro) and the individual level of the military policeman (micro) interferes with the phenomenon of police victimization on vacation hours? The hypothesis is that police victimization in PMMT and its risk factors are influenced by institutional and individual levels and reveals symptoms of a myriad of institutional and social problems, such as lack of sense of belonging, displacement of objectives or resignification of the military police function, family disintegration, among others. The research has a quantitative-qualitative approach, through the Tocqueville-Weber-Durkheim Method - TWD (Boudon e Cherkaoui, 1999). The data were collected through bibliographic research, documentary, online questionnaire, and in-depth individual interviews. The analysis is formal for quantitative data and informal for qualitative data. The results of the survey found that the risky lifestyle adopted by military police officers during the vacation period, on the other hand, the risk behavior adopted of military police during the period of vacation, such as: financial indebtedness of a serious nature; chemical dependence on legal and illicit drugs; frequency in risky places; carrying out a filler or a side job; building unrecommendable friendships; performing illegal activities; adopting police survival risky behaviors; adoption of risky conduct in personal/private life; and intervention in incidents during the holiday period, are the main causes of death of military policemen during the time off. In a complementary way, it was possible to understand the various motivations that lead military police officers to adopt their respective risk behaviors during the period of leave, revealing the difficulties of military policemen in carrying out a healthy or balanced management of their life, comprising not only the professional scope, but mainly the personal scope. The hypothesis has been confirmed, and the sociological reflexes, fruit of the causes and consequences of the victimization of military police during the period of leave, reveal the following institutional and individual problems, namely: the feeling of salary and institutional devaluation perceived by the surveyed military police officers, which causes the fall of the sense of belonging to the institution; the displacement of objectives or resignification of the military police function, so that military police activity is relegated to the background, that is, it becomes the “side job”, and the side job becoming the main activity of the Military police officer; and, at the individual level, the financial, family, emotional, interpersonal and integral disruption of the health of military policemen is a reality and a worrying diagnostic framework, and that deserves the subsequent scientific studies in the field of Collective Health.